From Trust to Ignorance: What does Journalism Mean to Young People in the Social Media Environment? - Lenčiauskienė, Patricija (Information & Media, 2025)
In recent years, the rapid development of digital technologies and the challenges it poses have led to a surge in research on youth experiences in the media environment. The changing media environment and the new content creators emerging in it challenge professional journalism and blur the boundaries between professional and non-professional content. Young people growing up in such an information environment develop news-related practices and attitudes that are significantly different from the practices and attitudes of previous generations, which determines how young people receive, consume and share information. Therefore, the aim of this article is to reveal what meaning young people give to journalism in the social media environment. The article presents a study which included 13 focus group interviews with 63 senior students from different Lithuanian high schools. Reflective thematic analysis of the data revealed that distrust of journalism (or even condemnation of it) stems from an emotionally based relationship between journalism and young people, determined by a lack of knowledge. This indicates the need to develop and implement journalistic tools, strategies and practices that, by taking into account the growing influence of social media and the changing behavior of young people, could reach the young audiences on social media platforms.
Keywords: young people; journalism; social media platforms; disinformation